Estratégias baseadas em reticulação de polímeros para evitar perdas de circulação em poços de petróleo - Trampus, Bruna Camara (2016)
Drilling operations with high e ciency and control is a topic of utmost interest in the exploration of oil and gas because it is directly linked to aspects of personal, environmental and economic safety. Many procedures should be performed for good control of the well. Among them, it is essential to maintain the well hydrostatic pressure higher than the pore pressure of the exposed formation, in order to avoid fluid influx, such as gas or oil, from the rock formation into the well. The need for a high hydrostatic pressure can lead to fractures in the rock formations, or they can be originally fractured, leading to a loss of drilling fluid into the formation and therefore the reduction of the hydrostatic pressure. Considering the facts mentioned, the present work aims to develop plugging fluids based on the crosslinking of poly (vinyl alcohol) (PVA) to seal the cracks of the rock formations and to prevent circulation loss. The study is conducted with respect to chemical crosslinking of the PVA, aiming to understand how the type of crosslinking agent, time, and temperature affect the crosslinked material. In addition, it assessed the use of crosslinked hydrogel for fissure obstruction. The results indicate that this methodology is very promising, because hydrogels crosslinked by the time under 30 min were able to withstand a pressure of 100psi for an hour without any leak.